Pola Relasi Gender dalam Keluarga Nikah Siri - Jalaludin, Akhmad; Sofiani, Triana (MUWAZAH: Jurnal Kajian Gender, 2020)
This paper analyzes the practice of siri marriages and patterns of gender relations in the siri marriage family in Pekalongan City. The theoretical argument that has been developed by the local people of Pekalongan City is that siri marriage is the same as registered marriage. This qualitative research with a gender perspective uses data collection techniques, i.e: observations, interviews, and literary studies. The technique of checking the credibility of the data uses triangulation and analysis using an interactive model. The results showed that the practice of siri marriage in Pekalongan City used a model, ie: performing an akad as a legal marriage, the only difference being the absence of a Marriage Registration Officer; came to the Kiai's house together with the guardian and the witness, and 3) the akad was carried out in secret at the Kiai's house. The causes of siri marriage in Pekalongan City, namely: fear of sin, avoiding adultery, economic hardship, polygamy that is not allowed by wives, a pregnancy outside of marriage, there is no fee for legal marriage and understanding of the meaning of marriage. The practice of unregistered marriage has an impact on women and children. The pattern of gender relations in the siri marriage family in Pekalongan City is in the form of a pseudo-vertical-hierarchical relationship pattern, where the husband has a higher position than the husband's wife has the power to regulate and make decisions in the household (subordination), but the roles, functions, and responsibilities of the husband do not implement optimally, or there is a deviation of roles, functions and responsibilities. Therefore, it is necessary to build awareness for perpetrators of unregistered marriages to create a pattern of relationships that are fair and gender-equal.